Fulvio Papi lettore di poesia (Materiali di Estetica. Terza serie, 2020)
My paper analyzes Fulvio Papi’s essays on poetry. First of all, I consider his reflecting and theoretical essays concerning the forms of philosophical questioning of poetry as a writing practice. I then examine his 2009 essay on Antonia Pozzi’s poetic production. Papi shows how the poet’s vital experience is transfigured in the compositional and enunciative rules of the text.
Keywords: Fulvio Papi; Poetic word; Composition; Antonia Pozzi